2016
DOI: 10.1186/s13256-016-1098-x
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset fetal growth restriction treated with the long-acting phosphodiesterase-5 inhibitor tadalafil: a case report

Abstract: BackgroundSevere early-onset fetal growth restriction occurs in 0.4 % of all pregnancies, and the prognoses of these patients are dismal. Severely growth-restricted fetuses (far below 500 g) are thought to be nonviable. Since there have not been effective treatments for such fetal patients, obstetricians have simply tried to identify the optimal timing for their delivery. There are a few reports suggesting that the phosphodiesterase type 5 inhibitor sildenafil has some limited beneficial effects on fetal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Tadalafil, a selective PDE5 inhibitor, has been used to treat pulmonary hypertension in pregnant women. We have recently shown a potential therapeutic effect for tadalafil on PE and FGR in small clinical trials 912 . In addition, our animal experiments have demonstrated that tadalafil treatment elevates maternal urinary excretion of cGMP and dilates the maternal blood sinuses in the placenta, which facilitates fetal growth 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Tadalafil, a selective PDE5 inhibitor, has been used to treat pulmonary hypertension in pregnant women. We have recently shown a potential therapeutic effect for tadalafil on PE and FGR in small clinical trials 912 . In addition, our animal experiments have demonstrated that tadalafil treatment elevates maternal urinary excretion of cGMP and dilates the maternal blood sinuses in the placenta, which facilitates fetal growth 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PDE5 inhibitors, which act by dilating arteries and increasing blood flow and are used to treat erectile dysfunction and pulmonary hypertension 6 , were suggested as a potential remedy for FGR 7 . Concurrently, our study showed that tadalafil, a selective PDE5 inhibitor, could be used in this manner [8][9][10][11][12] . However, the effect of L-NAME on the metabolic status of the offspring, as well as tadalafil's potential to modulate such outcomes, has not been investigated.…”
mentioning
confidence: 58%
“…It is hypothesized that sildenafil citrate may improve the uteroplacental blood flow of EO-FGR-affected pregnancies. [3][4][5]…”
Section: Introductionmentioning
confidence: 99%